2014
DOI: 10.5415/apallergy.2014.4.4.230
|View full text |Cite
|
Sign up to set email alerts
|

The role of antiseptic agents in atopic dermatitis

Abstract: The skin of individuals with atopic dermatitis has a susceptibility to be colonized with Staphylococcus aureus. This has been associated with increased frequency and severity of exacerbations of atopic dermatitis. Therefore, there is a growing interest in the use of antiseptic agents to target primary bacterial colonization and infection. Antiseptic agents have been found to be better tolerated and less likely to induce bacterial resistance as compared to antibiotics. There is also a wide variety of antiseptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 76 publications
0
26
0
3
Order By: Relevance
“…While available studies suggest some benefit to the use of such agents in AD management, good‐quality clinical data supporting their use are limited, particularly with regard to long‐term outcomes. Available data support the daily use of emollients and topical corticosteroids as a strategy to reduce colonisation . Regulatory authorities in Europe and the United States have removed triclosan from personal care soap products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While available studies suggest some benefit to the use of such agents in AD management, good‐quality clinical data supporting their use are limited, particularly with regard to long‐term outcomes. Available data support the daily use of emollients and topical corticosteroids as a strategy to reduce colonisation . Regulatory authorities in Europe and the United States have removed triclosan from personal care soap products.…”
Section: Discussionmentioning
confidence: 99%
“…20 Topical anti-staphylococcal agents are increasingly used as ancillary therapy for the management of AD, either clinically to manage existing infection or prophylactically in individuals who are at risk of colonisation or infection. 21 While available studies suggest some benefit to the use of such agents in AD management, good-quality clinical data supporting their use are limited, particularly with regard to long-term outcomes. Available data support the daily use of emollients and topical corticosteroids as a strategy to reduce colonisation.…”
Section: General Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…We gave weekly 0.005% NAOCl washes. Several studies have reported that 0.005% NaOCl showers were effective and safe in reducing S. aureus (including MRSA) infections and colonization in patients with atopic diseases (AD) [6][7][8][9][10]. NaOCl has been safely used in environmental cleaning and disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…At concentrations of 0.025-0.5%, NaOCl is used for treatment of wounds, burns, and decubitus ulcers [6]. Several studies have shown that NaOCl is safe at the concentration of 0.005% [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%